The Airline Industry: A Review of its Value Drivers and the Correlation between Capital Structure and Firm Performance - Arulampalam, Jeeva (2013)
There are two key objectives to this research. Firstly, it seeks to illustrate through four case studies how full-service carriers and low-cost carriers capitalise on their value drivers to strengthen firm performance. The subsequent objective is to explore the relationship between the capital structure and performance of airline companies. Based on a sample of 52 airlines spread throughout the globe, a correlation analysis was carried out using performance measures [return on equity (ROE), return on assets (ROA), and return on invested capital (ROIC)] and capital structure measures [debt ratio, debt-to-equity (D/E), long-term debt over total assets (LTDA) and Short-term debt over total assets (STDA)]. The results showed that there is a negative relationship between capital structure and firm‟s performance. However, the only significantly negative relationships exist between debt ratio, LTDA and STDA with dependent variable ROIC. The other significantly negative relationship is between debt ratio and ROA.